ChemInform Abstract: Asymmetric Synthesis of Spiro[chroman‐3, 3′‐pyrazol] Scaffolds with an All‐Carbon Quaternary Stereocenter via a Oxa‐Michael—Michael Cascade Strategy with Bifunctional Amine‐Thiourea Organocatalysts. Issue 10 (February 2016) - Zheng, Weiping; Zhang, Jiayong; Liu, Shuang; Yu, Chengbin; Miao, Zhiwei
Abstract: It is shown that the thiourea moiety and cyclohexyl scaffold of the employed bifunctional catalyst play a significant role in controlling the stereoselectivity of the oxa‐Michael‐Michael cascade reaction.